Relationship between Girls’ Participation in Sports Activities and Social Difficulties at College Level - Humaira Nawaz,; Mehboob Ullah Khan,; Irfan Ullah,; Fehmina Bibi,; Mehwish Manzoor,; Azmat Iqbal, (Al-Qanṭara, 2023)
Girls’ participation in sports has traditionally been labeled as "problematic" in sports literature. Muslim girl's engagement is frequently seen as being constrained by the society. This study was conducted to investigate how Pakistani female students engage in sports and how they view their participation to be constrained. Data was collected from39 teachers, 163 female students and their parents through a self made questionnaire. The data was analyzed through SPSS version 22 by using mean and correlation coefficient as statistical sources in order to determine the relationship between the girls’ participation and social difficulties. The findings demonstrated that the association between girls’ participation in sports activities and societal challenges is significant and because of the constraints imposed by society, female students either do not participate or participate very little. Keywords: Girls’ participation, Sports activities, Social difficulties, College level